2020
DOI: 10.1002/ppul.24620
|View full text |Cite
|
Sign up to set email alerts
|

Community and caregivers’ perceptions of pneumonia and care‐seeking experiences in Nigeria: A qualitative study

Abstract: BackgroundAppropriate and timely care seeking can reduce pneumonia deaths, but are influenced by caregivers and community norms of health and illness. We explore caregiver and community perceptions, and care seeking experience, of childhood pneumonia, to understand contexts that drive paediatric service uptake in Nigeria. Methods Community group discussions and qualitative interviews with caregivers in Lagos and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 25 publications
4
25
3
Order By: Relevance
“…Some mothers, fathers and other caregivers associated pneumonia with exposure to cold environment/air. A similar finding have been noted in qualitative studies conducted in Ghana and Nigeria [25,26]. While illness conceptualization play an important role in the decision regarding treatment options [27,28], knowledge of biomedical causes alone may not lead to healthcare-seeking from facilities in settings where traditional beliefs are pervasive [29,30].…”
Section: Discussionsupporting
confidence: 77%
“…Some mothers, fathers and other caregivers associated pneumonia with exposure to cold environment/air. A similar finding have been noted in qualitative studies conducted in Ghana and Nigeria [25,26]. While illness conceptualization play an important role in the decision regarding treatment options [27,28], knowledge of biomedical causes alone may not lead to healthcare-seeking from facilities in settings where traditional beliefs are pervasive [29,30].…”
Section: Discussionsupporting
confidence: 77%
“…However, some caregivers who were conversant with the condition described it as critical. The authors revealed that inadequate knowledge of pneumonia in the study hints at poor healthcare seeking for the illness (Bakare et al, 2020). Another study among caregivers in rural and urban communities in Kaduna found their level of awareness to be high, and misconceptions about the causes of pneumonia were also high (67%).…”
Section: Knowledge Of the Primary Caregivers (Mothers Of Under-five Children) About Iccm Conditionsmentioning
confidence: 92%
“…Predictably, variations exist in the level of knowledge for each iCCM condition among different categories of caregivers in different social settings. A systematic review of publications on iCCM conditions across developing countries revealed that the caregivers' understanding of pneumonia-specific signs and symptoms was comparatively lower than that of malaria and diarrhea (Bakare et al, 2020;Geldsetzer et al, 2014).…”
Section: Knowledge Of the Primary Caregivers (Mothers Of Under-five Children) About Iccm Conditionsmentioning
confidence: 99%
“…Maternal and child health services are provided free at selected facilities, but out of pocket costs still pose a nancial barrier to access. [4] Kiyawa LGA was selected through discussion between Save the Children Nigeria, the State Ministry of Health (SMOH) and the Jigawa State Government, using pre-de ned criteria (e.g. mortality burden, road access).…”
Section: Settingmentioning
confidence: 99%
“…vaccine coverage and clean cooking) [3] and multiple misconceptions. [4] Diverse stakeholders prioritised the strengthening of primary care and community knowledge to tackle pneumonia in the context of Jigawa State. [5] Several community-based participatory empowerment approaches for improving maternal, neonatal and child health outcomes have been trialled.…”
Section: Introductionmentioning
confidence: 99%